RISK FACTORS ASSOCIATED WITH BIRTH ASPHYXIA - AHMAD , T; SYED , N; MEHREEN , B; RASHID , N; AHMAD , M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to identify factors contributing to prenatal asphyxia in full-term neonates born at Hayatabad Medical Complex in Peshawar. The research was conducted over one year (January 2022 to January 2023) at the Pediatrics Department of Hayatabad Medical Complex in Peshawar. The study involved mothers delivering twins vaginally, comprising 100 newborns with gestational ages between 37 and 42 weeks and birth weights from 2,000 to 4,000 grams. A case-control design was employed, categorizing infants with Apgar scores of five or less at one minute as cases and those with scores exceeding five as controls. Data collection utilized a customized form, capturing demographic variables and risk factors. Statistical analysis employed SPSS version 26.0, applying the chi-square test for comparison. The results showed significant differences between cases and controls regarding gender distribution, birth weight, mode of delivery, maternal age, and gestational age. Key risk factors, including parity, fetal distress, meconium in amniotic fluid, and prolonged labor, displayed significant differences between cases and controls. The study concluded that birth asphyxia is influenced by factors such as meconium-stained amniotic fluid, prolonged labor, and fetal distress. Obstetrician involvement in ongoing research enhances data reliability. Community-specific risk factors underscore the need for tailored interventions to mitigate birth asphyxia. Despite study limitations, including a single-center design, the findings contribute valuable insights for future research and targeted strategies.